13 Reasons Why the Rape Myth Survives. Issue 2 (1st July 2019) - Letort, Delphine
Abstract : The controversies triggered by the Netflix adaptation of Jay Asher's young adult novel Thirteen Reasons Why (2007) have focused on suicide and downplayed discussions of rape as a central plot device. Making use of stereotypical characters (such as the cheerleader and the jock) and archetypal setting (including the high school), 13 Reasons Why delves into the reassuring world of the suburban town; it deals ambiguously with the entwined notions of gender and power encapsulated in the teenpic genre. A detailed analysis of the series indeed reveals that its causative narrative reinforces the rape myth by putting the blame on girls for events that happen to them. In this article I explore the tensions of a TV series that endorses the rape myth through the entertaining frame of the teenpic.